Mathematical Model of Boundary Layer Flow over a Moving Plate in a Nanofluid with Viscous Dissipation - Muhammad Khairul Anuar, Mohamed; Nor Aida Zuraimi, Md Noar; Mohd Zuki, Salleh; Anuar, Ishak (JAFM, 2016)
In this study, the numerical investigation of boundary layer flow over a moving plate in a nanofluid with viscous dissipation and constant wall temperature is considered. The governing non-linear partial differential equations are first transformed into a system of ordinary differential equations using a similarity transformation. The transformed equations are then solved numerically using the Keller-box method. Numerical solutions are obtained for the Nusselt number, Sherwood number and the skin friction coefficient as well as the concentration and temperature profiles. The features of the flow and heat transfer characteristics for various values of the Prandtl number, plate velocity parameter, Brownian motion and thermopherosis parameters, Eckert number and Lewis number are analyzed and discussed. It is found that the presence of viscous dissipation reduces the range of the plate velocity parameter for which the solution exists. The increase of both Brownian motion and thermophoresis parameters results to the decrease of the Nusselt number, while the Sherwood number increases with the increase of the thermophoresis parameter.